Student acculturation in the context of "feesmustfall" - Jogee, R.; Callaghan, N.C.; Callaghan, C.W. (South African Journal of Higher Education, 2018)
This research seeks to investigate constraints to acculturation, or cultural adaptation to the university context, applying Berry’s acculturation theory as its theoretical framework. Predictions of acculturation theory are tested using a sample of 251 first year Economics students. According to acculturation theory, acculturation orientations are determined by the interactive strength of two individual dimensions, namely (i) a desire to maintain one’s own culture, and (ii) desire to acculturate to popular culture, with combinations of these processes classified as assimilation, separation, marginalisation or integration. What is absent from the predictions of acculturation theory (which are premised on the individual level), however, is a consideration of individual-level differences which are not theoretically ascribed to cultural influences, but which derive from the individual, such as those predicted by personality theory. This study therefore uses logistic regression analysis to test theory predicting the likelihood that students fall into each of Berry’s four acculturation orientations, while also testing personality dimensions as explanatory factors. Neuroticism and age are found to be negative and significant predictors of likelihood to fall into the separation explanatory category. Female students and those older than their cohorts are found to be more likely to fall into the marginalisation category. Agreeableness is negatively associated with marginalisation. Implications of these findings are discussed, and recommendations are derived for university management in order to improve acculturation of students in this context.